Harmaline-Induced Tremor in Mice: Videotape Documentation and Open Questions About the Model. (9th December 2013) - Cheng, Melody M.; Tang, Guomei; Kuo, Sheng-Han
Background: Harmaline-induced tremor in rodents has been extensively used as an animal model for essential tremor (ET). However, there is no visual documentation in the published literature. Methods: We injected mice subcutaneously with either 20 mg/kg of harmaline hydrochloride or saline and then videotaped the responses. Results: Action and postural tremor in the mouse began 5 minutes after subcutaneous harmaline injection and peaked at approximately 30 minutes. The tremor involved the head, trunk, tail, and four limbs and lasted for approximately 2 hours. The forelimb tremor was postural or action tremor, similar to that observed in ET. Discussion: This video segment provides the first visual documentation of the phenomenology of harmaline-induced tremor in a mouse. We also raise several unanswered questions regarding the use of harmaline-induced tremor to model ET.